Highly thermally conductive silicone gel for electronic components and method for preparing the same

CN122958870APending Publication Date: 2026-10-23ANHUI MINGXUN NEW MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411423764.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]本发明要解决现有应用于电子元器件的硅凝胶热导率低的问题,而提供一种用于电子元器件的高导热硅凝胶及其制备方法

Benefits of technology

[0020]有益效果:与现有技术相比,本发明采用表面改性有氨基硅烷层以及不饱和酰胺层的金属氧化物作为导热填料,利用其表面含有的不饱和碳碳双键与多氢硅油之间的加成反应,使得所述导热填料与硅凝胶内部的有机硅架构通过牢固的化学键结合,实现导热填料在硅凝胶中更优异的分散均匀性,获得导热系数不低于2.5W/m·K的硅凝胶,且该硅凝胶还具有利于应用的硬度以及利于热量传导的最薄可压缩厚度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a high-thermal-conductivity silicon gel for electronic components and a preparation method thereof, the high-thermal-conductivity silicon gel is prepared from double-terminated vinyl silicone oil as base glue, polyhydrogen silicone oil as crosslinking agent and chain extender, and modified metal oxide as thermal-conductivity filler, the modified metal oxide is introduced into the molecular structure of the silicon gel by using the amino silane layer and the unsaturated amide layer grafted on the surface of the modified metal oxide and the addition of the polyhydrogen silicone oil, the compatibility of the modified metal oxide as the thermal-conductivity filler with the silicon gel is greatly improved, the obtained silicon gel has a thermal conductivity coefficient of not less than 2.5 W / m*K, moderate hardness, and small compressible thickness of the thinnest, which is beneficial to the adhesion with electronic components and the heat transfer between the electronic components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic component materials, and more particularly to a high thermal conductivity silicon gel for electronic components and its preparation method. Background Technology

[0002] Currently, electronic components are becoming increasingly integrated, with devices trending towards lighter weight, smaller size, and higher power density. This results in a significant increase in the amount of heat generated inside these components. The accumulation of this heat can substantially impact the lifespan of electronic components or even cause them to fail. Some scholars have suggested that the failure of Moore's Law is partly due to the large amount of heat generated by electronic components. Therefore, effectively and quickly dissipating the significant amounts of heat generated by electronic components has become a pressing issue.

[0003] Currently, to address the heat dissipation problem of electronic components, thermal management materials and related active, passive, and integrated cooling technologies have seen unprecedented development. Thermal management materials can be categorized into metals, ceramics, semiconductors, electronic glass, polymers, PCB materials, and thermal interface materials (TIMs). TIMs are widely used for heat dissipation in electronic packaging and components. While chips, graphics cards, or other heat sources in electronic components appear to be in close contact with heat sinks on a macroscopic scale, microscopically, the contact between solids is not perfect. The contact occurs only on discrete area elements, with air filling the gaps between them. Since air has a thermal conductivity of only 0.023 W / m·K, it can be approximated as adiabatic, which is highly detrimental to the removal of heat generated from the heat source from the electronic components. TIMs can fill the holes and gaps created when two solid materials come into contact, expelling air from the holes or gaps. Furthermore, TIMs have a high κ value, which is more conducive to heat conduction, thereby improving heat dissipation.

[0004] Common thermal interface materials (TIMs) include thermal grease, thermal adhesive, thermal pads, thermal phase change materials, thermal graphite sheets, and thermal silicone gels. Thermal silicone gel is a composite of liquid silicone rubber and thermally conductive fillers. Its performance falls between that of thermal grease and thermal pads, combining the advantages of both, and it is gradually replacing both. The earliest thermal silicone gel was a product produced by Parker Gumballs in the early 2000s, a form between thermal grease and thermal silicone pads. Currently, the high-end thermal interface material market is dominated by companies from developed countries such as the United States, Japan, and Germany. Research on thermal silicone gel in China started relatively late, and the technology is not yet mature. Domestic products mainly occupy the low-to-mid-range market. With further advancements in chip manufacturing technologies and the expansion of applications, China, as the future main force in electronic integrated packaging, will further improve its chip packaging technology, leading to a huge demand for thermally conductive packaging materials such as thermal silicone gel. The market size of thermal silicone gel is expected to experience rapid expansion in the next 5-7 years. Therefore, the research and preparation of high-performance thermally conductive silicone gels has very important practical significance and huge economic value.

[0005] A common method to improve the thermal conductivity of silica gel is to fill it with a large amount of highly thermally conductive material. Currently, fillers include ceramic materials such as alumina, boron nitride, and aluminum nitride, and highly thermally conductive carbon materials such as graphene and carbon nanotubes. Medium thermal conductivity fillers require a volume fraction of over 50% to achieve the desired thermal conductivity, while highly thermally conductive carbon materials are typically expensive and are good electrical conductors, thus limiting the filler volume. Summary of the Invention

[0006] The present invention aims to solve the problem of low thermal conductivity of existing silicon gels used in electronic components, and provides a high thermal conductivity silicon gel for electronic components and its preparation method.

[0007] A high thermal conductivity silicone gel, by weight, comprises the following raw materials: 100-150 parts of double-terminated vinyl silicone oil, 20-40 parts of polyhydrogen silicone oil, 0.3-0.5 parts of platinum catalyst, 0.6-1.2 parts of inhibitor, 0-0.4 parts of reinforcing agent, and 200-250 parts of thermally conductive filler; wherein the thermally conductive filler is a modified metal oxide, and the modified metal oxide is obtained by amylation modification of at least one of beryllium oxide, magnesium oxide, aluminum oxide, and zinc oxide.

[0008] In some embodiments of the present invention, the concentration of vinyl groups in the dual-terminated vinyl silicone oil is 0.12-0.20 mmol / g, and the viscosity is 400-600 cst.

[0009] In some embodiments of the present invention, the hydrogen concentration of the polyhydrosilicone oil is 0.95-0.98 mmol / g, and the viscosity is 90-120 cst.

[0010] In some embodiments of the present invention, the molar ratio of alkenyl groups in the double-terminated vinyl silicone oil to silane-hydrogen bonds in the polyhydrogen silicone oil is 1:1.2-1.5.

[0011] In some embodiments of the present invention, the inhibitor is at least one selected from 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane, 1-ethynylcyclohexanol, 2-methylbutynol, diethyl fumarate, and diallyl maleate.

[0012] In some embodiments of the present invention, the method for preparing the thermally conductive filler includes the following steps: S1: Dissolve the metal oxide in deionized water and disperse it thoroughly by ultrasonication. Dissolve 10-15% of the metal oxide's mass in aminosilane in deionized water and stir to disperse it evenly. Add the dispersed metal oxide to the evenly dispersed aminosilane solution and stir. React at a constant temperature of 60-75℃ for 13-15 hours. After the reaction is complete, separate by centrifugation, and then wash, filter, and dry. S2: Unsaturated aminocarboxylic acid and oxalyl chloride are mixed in an organic solvent and subjected to an acyl halide reaction. During the reaction, a weak acid salt is continuously added dropwise for neutralization. When all the carboxylic acid in the system is converted into acyl chloride, the powder obtained in S1 is added to it. The mixture is heated under reflux for 8-10 hours, cooled to room temperature, centrifuged, washed and dried to obtain the thermally conductive filler.

[0013] Further, in S2, the unsaturated aminocarboxylic acid is at least one of 2-amino-2-methyl-3-pentenoic acid, 4-amino-3-chloro-2-pentenic acid, (E)-4-morpholinobut-2-enoic acid, 3,4-dehydro-DL-proline, and (1R,4S)-N-tert-butoxycarbonyl-1-aminocyclopent-2-ene-4-carboxylic acid.

[0014] Furthermore, the unsaturated amino acid is at least one of 2-amino-2-methyl-3-pentenoic acid and 4-amino-3-chloro-2-pentenic acid.

[0015] Further, in S2, the organic solvent is at least one of dichloroethane, carbon tetrachloride, and toluene; the weak acid salt is at least one of sodium carbonate, sodium bicarbonate, potassium carbonate, and potassium bicarbonate; and the molar ratio of the carboxyl group of the unsaturated aminocarboxylic acid to oxalyl chloride is 1:1-1.2.

[0016] The preparation method of the high thermal conductivity silicone gel described above includes the following steps: dispersing a platinum catalyst in a multi-hydrogen silicone oil, then adding a thermally conductive filler, stirring evenly at room temperature, and after reacting for 3-4 hours, adding a double-terminated vinyl silicone oil, an inhibitor, and a reinforcing agent, stirring thoroughly, and reacting again for 3-4 hours. After dispersion and reaction are completed, the sample is taken out and vacuumed and degassed in a vacuum drying oven to obtain the high thermal conductivity silicone gel.

[0017] When preparing silicone gels, excessively high viscosity of the dual-terminated vinyl silicone oil significantly reduces its powder capacity, hindering the improvement of thermal conductivity and sample processing. Conversely, excessively low viscosity prevents widely distributed low-molecular-weight molecules from participating in the reaction, failing to form a stable network structure and ultimately leading to the precipitation of low-molecular-weight organic matter, which contaminates electronic components. Therefore, preferably, the viscosity of the dual-terminated vinyl silicone oil used in this invention is 400-600 cSt, and the viscosity of the polyhydrogen silicone oil used is 90-120 cSt.

[0018] However, during the preparation of the high thermal conductivity silicone gel, the polyhydrogen-based silicone oil in the system reacts not only with the carbon-carbon double bonds in the double-terminated vinyl silicone oil, but also with the unsaturated double bonds on the surface of the thermally conductive filler. If the carbon-carbon double bonds and silicon-hydrogen bonds in the silicone oil react completely or there is an excess of silicon-hydrogen bonds, on the one hand, it will affect the flexibility of the resulting silicone gel, causing it to not fully adhere to other heat sources in electronic components; on the other hand, the thermally conductive filler can only achieve dispersion within the system through hydrogen bonds forming forces with the silicone gel, which easily leads to a series of application problems at high temperatures due to the inability of the thermally conductive filler to maintain good dispersion uniformity. Based on this, the inventors have found through experiments that, in order to obtain a high thermal conductivity silicone gel with better application performance, the preferred mass ratio of thermally conductive filler to polyhydrogen-based silicone oil is 6-10:1.

[0019] In this invention, the thermally conductive filler is obtained by grafting amino groups onto the surface of a specific metal oxide, followed by an amidation reaction between the amino group and an unsaturated aminocarboxylic acid. The addition of unsaturated carbon-carbon bonds and silicon-hydrogen bonds on the surface of the thermally conductive filler allows it to chemically bond with the silica gel. This not only solves the problem of poor dispersion of the thermally conductive filler in the silica gel but also forms a uniform thermally conductive pathway within the silica gel, improving its thermal conductivity. The unsaturated aminocarboxylic acid used acts as a bridge between the metal oxide and the organosilicon structure in the silica gel; its structure significantly influences the thermal conductivity and mechanical properties of the final silica gel. Through experimentation, the inventors ultimately selected the aforementioned unsaturated aminocarboxylic acid to prepare the thermally conductive filler, aiming to obtain a high-thermal-conductivity silica gel with excellent thermal conductivity and low compression set.

[0020] Beneficial effects: Compared with the prior art, the present invention uses metal oxides with surface-modified aminosilane layers and unsaturated amide layers as thermally conductive fillers. By utilizing the addition reaction between the unsaturated carbon-carbon double bonds on its surface and polyhydrogen silicone oil, the thermally conductive filler is strongly bonded to the organosilicon structure inside the silicone gel through chemical bonds. This achieves better dispersion uniformity of the thermally conductive filler in the silicone gel, resulting in a silicone gel with a thermal conductivity of not less than 2.5 W / m·K. Furthermore, the silicone gel also has hardness that is beneficial for application and a minimum compressible thickness that facilitates heat conduction. Detailed Implementation

[0021] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0022] The following exemplarily illustrates the preparation process of the thermally conductive filler used in the embodiments: Thermally conductive filler-1 S1: Dissolve 25g of beryllium oxide in deionized water and disperse it thoroughly by ultrasonication. Dissolve 2.5g of di(3-trimethoxysilylpropyl)amine in deionized water and stir to disperse it evenly. Add the dispersed beryllium oxide to the evenly dispersed di(3-trimethoxysilylpropyl)amine solution and stir. React at a constant temperature of 60℃ for 13h. After the reaction is completed, separate by centrifugation, and wash, filter and dry. S2: 12.9 g (0.1 mol) of 2-amino-2-methyl-3-pentenoic acid and 12.7 g (0.1 mol) of oxaloyl chloride were mixed in 100 ml of dichloroethane to carry out an acyl halide reaction. Sodium carbonate was continuously added to neutralize the reaction. When all the carboxylic acids in the system were converted into acyl chlorides, the powder obtained in S1 was added to the mixture. The mixture was heated to 85 °C and refluxed for 8 h. After cooling to room temperature, the mixture was centrifuged, washed, and dried to obtain the thermally conductive filler-1.

[0023] Thermally conductive filler-2 S1: Dissolve 25g of magnesium oxide in deionized water and disperse it thoroughly by ultrasonication. Dissolve 3.0g of diethylenetriaminopropyltrimethoxysilane in deionized water and stir to disperse it evenly. Add the dispersed magnesium oxide to the evenly dispersed diethylenetriaminopropyltrimethoxysilane solution and stir. React at a constant temperature of 70℃ for 14h. After the reaction is completed, separate by centrifugation, and wash, filter and dry. S2: 17.1 g (0.1 mol) (E)-4-morpholinobut-2-enoic acid and 13.9 g (0.11 mol) oxalyl chloride were mixed in 100 ml of carbon tetrachloride to carry out an acyl halide reaction. Potassium carbonate was continuously added to neutralize the reaction. When all the carboxylic acids in the system were converted into acyl chlorides, the powder obtained in S1 was added to the mixture. The mixture was heated to 95 °C and refluxed for 9 h. After cooling to room temperature, the mixture was centrifuged, washed, and dried to obtain the thermally conductive filler-2.

[0024] Thermally conductive filler-3 S1: Dissolve 25g of alumina in deionized water and disperse it thoroughly by ultrasonication. Dissolve 3.75g of KH-540 in deionized water and stir to disperse it evenly. Add the dispersed alumina to the evenly dispersed KH-540 solution and stir. React at a constant temperature of 75℃ for 15h. After the reaction is complete, separate by centrifugation, and wash, filter and dry. S2: 22.7 g (0.1 mol) (1R,4S)-N-tert-butoxycarbonyl-1-aminocyclopent-2-ene-4-carboxylic acid and 15.2 g (0.12 mol) oxalyl chloride were mixed in 100 ml toluene to carry out an acyl halide reaction. Potassium bicarbonate was continuously added to neutralize the reaction. When all the carboxylic acids in the system were converted to acyl chloride, the powder obtained in S1 was added to the mixture. The mixture was heated to 115 °C and refluxed for 10 h. After cooling to room temperature, the mixture was centrifuged, washed, and dried to obtain the thermally conductive filler-3.

[0025] The dual-terminated vinyl silicone oil, hydrogen-containing silicone oil, and platinum-based catalysts used in the following examples and comparative examples were all purchased from Ambia Specialty Silicones (Nantong) Co., Ltd.

[0026] Example 1 Disperse 0.3 parts of diethylenetetramethyldisiloxane platinum complex (containing 0.5% platinum) in 100 parts of Andisil ® Add 250 parts of thermally conductive filler-1 and 20 parts of Andisil to VS500 (vinyl content 0.15 mmol / g). ® XL 1B (0.95 mmol / g) was stirred evenly at room temperature. After reacting for 3 hours, 0.6 parts of 1,3,5,7-tetravinyl-1,3,5,7-tetramethylcyclotetrasiloxane and 0.4 parts of silica were added. After stirring thoroughly, the mixture was reacted again for 3 hours. After dispersion and reaction were completed, the sample was removed and vacuumed and degassed in a vacuum drying oven to obtain the high thermal conductivity silica gel.

[0027] Example 2 0.4 parts of diethylenetetramethyldisiloxane platinum complex (containing 0.5% platinum) were dispersed in 120 parts of Andisil ®In VS500, 230 parts of thermally conductive filler-2 and 30 parts of Andisil® XL 1B were added and stirred evenly at room temperature. After reacting for 3.5 hours, 0.9 parts of 1-ethynylcyclohexanol and 0.2 parts of silica were added and stirred thoroughly. The mixture was then reacted again for 3.5 hours. After dispersion and reaction were completed, the sample was removed and vacuumed and degassed in a vacuum drying oven to obtain the high thermal conductivity silicone gel.

[0028] Example 3 Disperse 0.5 parts of diethylenetetramethyldisiloxane platinum complex (containing 0.5% platinum) in 150 parts of Andisil ® In VS500, 200 parts of thermally conductive filler-3 and 40 parts of Andisil® XL 1B were added and stirred evenly at room temperature. After reacting for 4 hours, 1.2 parts of diethyl fumarate and 0.1 parts of silica were added and stirred thoroughly. After reacting for another 4 hours, the sample was taken out and vacuumed and degassed in a vacuum drying oven to obtain the high thermal conductivity silicone gel.

[0029] Example 4 Same as Example 3, except that Andisil is used. ® The number of VS500 copies is 169. At this time, Andisil ® The molar ratio of alkenyl groups in VS500 to silane bonds in Andisil® XL 1B is 1:1.5.

[0030] Example 5 Same as Example 3, except that the number of parts of thermally conductive filler-3 used is 240.

[0031] Comparative Example 1 Similar to Example 3, except that the thermally conductive filler used is only modified with aminosilane surface.

[0032] Comparative Example 2 Same as Example 3, except that the thermally conductive filler used is unmodified alumina.

[0033] Comparative Example 3 Same as Example 3, except that no thermally conductive filler is added.

[0034] Performance testing Thermal conductivity: Thermal conductivity was tested according to ASTM-D5470 standard; Shore hardness: The Shore hardness was tested using an AICE Shore 00 rubber hardness tester according to the ASTM-D2240 standard. Thinnest compressible thickness (BLT): BLT is measured using a micrometer and two identical glass slides. First, the thickness of one glass slide and the thickness of two glass slides tightly adhered together are measured separately using the micrometer. Then, a certain amount of thermally conductive silicone gel sample is added to the same location and pressed thoroughly. Excess sample squeezed out of the glass slides is wiped away. Pressing continues until no more sample flows out of the glass slides. At this point, the overall thickness of the sample and the glass slides is measured. Then, the thickness of the glass slides is calculated by subtracting the thickness of the glass slides from the overall thickness of the sample and the glass slides. The BLT of the thermally conductive silicone gel is then obtained.

[0035] The test results are shown in Table 1:

[0036] As shown in Table 1, the silicone gel provided by this invention has a thermal conductivity of not less than 2.5 W / m·K and a Shore hardness between 40 and 45, making it easy to perfectly fit with heat sources and heat sinks. It also provides a certain buffering protection when electronic components or other heat sources are impacted. The minimum compressible thickness of not more than 151 μm is also beneficial for heat conduction.

[0037] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A high thermal conductivity silicone gel, characterized in that, The product comprises, by weight parts, the following raw materials: 100-150 parts of double-terminated vinyl silicone oil, 20-40 parts of polyhydrogen silicone oil, 0.3-0.5 parts of platinum catalyst, 0.6-1.2 parts of inhibitor, 0-0.4 parts of reinforcing agent, and 200-250 parts of thermally conductive filler; wherein the thermally conductive filler is a modified metal oxide, and the modified metal oxide is obtained by amylation or amidation modification of at least one of beryllium oxide, magnesium oxide, aluminum oxide, and zinc oxide.

2. The high thermal conductivity silica gel according to claim 1, characterized in that, The concentration of carbon-carbon double bonds in the double-terminated vinyl silicone oil is 0.12-0.20 mmol / g, and the viscosity is 400-600 cst.

3. The high thermal conductivity silica gel according to claim 1, characterized in that, The concentration of the polyhydrogen-based silicone oil used is 0.95-0.98 mmol / g, and the viscosity is 90-120 cst.

4. The high thermal conductivity silicone gel according to claim 1, characterized in that, The molar ratio of alkenyl groups in the double-terminated vinyl silicone oil to silane-hydrogen bonds in the polyhydrogen silicone oil is 1:1.2-1.

5.

5. The high thermal conductivity silicone gel according to claim 1, characterized in that, The mass ratio of the thermally conductive filler to the polyhydrosilicone oil is 6-10:

1.

6. The high thermal conductivity silicone gel according to claim 1, characterized in that, The method for preparing the thermally conductive filler includes the following steps: S1: Dissolve the metal oxide in deionized water and disperse it thoroughly by ultrasonication. Dissolve 10-15% of the metal oxide's mass in aminosilane in deionized water and stir to disperse it evenly. Add the dispersed metal oxide to the evenly dispersed aminosilane solution and stir. React at a constant temperature of 60-75℃ for 13-15 hours. After the reaction is complete, separate by centrifugation, and then wash, filter, and dry. S2: Unsaturated aminocarboxylic acid and oxalyl chloride are mixed in an organic solvent and subjected to an acyl halide reaction. During the reaction, a weak acid salt is continuously added dropwise for neutralization. When all the carboxylic acid in the system is converted into acyl chloride, the powder obtained in S1 is added to it. The mixture is heated under reflux for 8-10 hours, cooled to room temperature, centrifuged, washed and dried to obtain the thermally conductive filler.

7. The high thermal conductivity silicone gel according to claim 6, characterized in that, In S2, the unsaturated aminocarboxylic acid is at least one of 2-amino-2-methyl-3-pentenoic acid, 4-amino-3-chloro-2-pentenoic acid, (E)-4-morpholinobut-2-enoic acid, 3,4-dehydro-DL-proline, and (1R,4S)-N-tert-butoxycarbonyl-1-aminocyclopent-2-ene-4-carboxylic acid.

8. The high thermal conductivity silicone gel according to claim 7, characterized in that, The unsaturated aminocarboxylic acid is at least one of 2-amino-2-methyl-3-pentenoic acid and 4-amino-3-chloro-2-pentenic acid.

9. The high thermal conductivity silicone gel according to claim 6, characterized in that, In S2, the organic solvent is at least one of dichloroethane, diethyl ether, carbon tetrachloride, and toluene; the weak acid salt is at least one of sodium carbonate, sodium bicarbonate, carbonic acid, and potassium bicarbonate; and the molar ratio of the unsaturated aminocarboxylic acid to oxaloyl chloride is 1:1-1.

2.

10. A method for preparing the high thermal conductivity silica gel according to any one of claims 1-9, characterized in that, The process includes the following steps: dispersing a platinum catalyst in a multi-hydrogen silicone oil, then adding a thermally conductive filler, stirring evenly at room temperature, and after reacting for 3-4 hours, adding a double-terminated vinyl silicone oil, an inhibitor, and a reinforcing agent, stirring thoroughly, and reacting again for 3-4 hours. After dispersion and reaction are completed, the sample is taken out and vacuumed and debubbled in a vacuum drying oven to obtain the high thermal conductivity silicone gel.